Influence of Titration of Neurohormonal Antagonists and Blood Pressure Reduction on Renal Function and Decongestion in Decompensated Heart Failure - Kula, Alexander J. (Circ Heart Fail, 2015)
BACKGROUND: Reduction in systolic blood pressure (SBP reduction) during the treatment of acute decompensated heart failure (ADHF) is strongly and independently associated with worsening renal function (WRF). Our objective was to determine if SBP reduction or titration of oral neurohormonal antagonists during ADHF treatment negatively influences diuresis and decongestion. METHODS AND RESULTS: SBP reduction was evaluated from admission to discharge in consecutive ADHF admissions (n=656). Diuresis and decongestion was examined across a range of parameters such as diuretic efficiency, fluid output, hemoconcentration, and diuretic dose. The average reduction in SBP was 14.4 ± 19.4 mmHg and 77.6% of the population had discharge SBP lower than admission. SBP reduction was strongly associated with WRF (OR=1.9, 95% CI: 1.2-2.9, p=0.004), a finding that persisted after adjusting for parameters of diuresis and decongestion (OR=2.0, 95% CI: 1.3-3.2, p=0.002). However, SBP reduction did not negatively impact diuresis or decongestion (p≥0.25 for all parameters). Uptitration of neurohormonal antagonists occurred in over 50% of admissions and was associated with a modest additional reduction in blood pressure (≤ 5.6 mmHg). Notably, WRF was not increased and diuretic efficiency was significantly improved with the uptitration of neurohormonal antagonists. CONCLUSIONS: Despite a higher rate of WRF, blood pressure reduction was not associated with worsening of diuresis or decongestion. Furthermore, titration of oral neurohormonal antagonists was actually associated with improved diuresis in this cohort. These results provide reassurance that the guideline recommended titration of chronic oral medication during ADHF hospitalization may not be antagonistic to the short-term goal of decongestion.